2012
DOI: 10.1071/cp12123
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the potential contributions of N2 fixation by legumes in Australian pasture systems

Abstract: The amounts of foliage nitrogen (N) fixed by various annual and perennial legumes growing in Australian pastures range from <10 to >250 kg N/ha.year. Differences in N2 fixation result from variations in the proportion of the legume-N derived from atmospheric N2 (%Ndfa) and/or the amount of legume-N accumulated during growth. On-farm surveys of %Ndfa achieved by legumes growing in farmers’ paddocks in Australia indicated that N2 fixation contributed >65% of the legume’s N requirements in three-quarters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 186 publications
2
73
2
Order By: Relevance
“…We found that the process of crop residue decomposition added additional mineral N to the soil N pools. By contrast, the summerfallow system lost soil N during the postharvest period, whereas the cereal monoculture systems had little or no change in postharvest soil N. The soil N dynamics are complicated 40 , and the quantity of soil N can change with many factors 41,42 . In the present study, the largest change in soil N over the postharvest period occurred in the fall 2007 to spring 2008 period when the summerfallow fields lost 63.9 N kg ha −1 , whereas the fields after pulses increased soil N by 25.3 kg ha −1 , and the fields after wheat increased by 18.5 kg ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the process of crop residue decomposition added additional mineral N to the soil N pools. By contrast, the summerfallow system lost soil N during the postharvest period, whereas the cereal monoculture systems had little or no change in postharvest soil N. The soil N dynamics are complicated 40 , and the quantity of soil N can change with many factors 41,42 . In the present study, the largest change in soil N over the postharvest period occurred in the fall 2007 to spring 2008 period when the summerfallow fields lost 63.9 N kg ha −1 , whereas the fields after pulses increased soil N by 25.3 kg ha −1 , and the fields after wheat increased by 18.5 kg ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…During the KohnRot trial from 1963 to 1981 the soil N accumulation rate of 45-65 kg N/ha/year was associated with N fixation rates of 95-113 kg N/ha/year (Helyar et al, 1997). In general, modern pasture systems have the potential to fix ∼250 kg N/ha/year due to improved varieties and inoculants, and better management of soil constraints (Peoples et al, 2012), hence the potential for soil N accumulation has improved.…”
Section: The Management Of N In Crop -Pasture Rotationsmentioning
confidence: 98%
“…Therefore, the use of the d 15 N of N 2 -fixing legume shoots for the term d 15 N leg (eN) in Equation (4) actually implies that of all of the possible sources of legume N and pathways that can contribute to N transfer to a non-legume (Table 1), only aboveground fixed N was transferred. Given the potential size of below-ground pool of legume N and rhizosphere deposition of N (Fustec et al, 2010;Peoples et al, 2012), and reports that intercropping enhances root production and turnover of fine roots (Lehmann and Zech, 1998), a first approximation for N sources for transfer might more plausibly equate to a below-ground pathway of transfer of fixed N from the roots and/or nodules rather than above-ground sources of fixed N. This would particularly the case for annuals where opportunities for N contributions from foliage will be limited during a single growing season. Below-ground Bergersen et al (1988), Boddey et al (2000), Unkovich et al (2008Unkovich et al ( , 2000, and Unkovich ( 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 sources of N are also likely to be important in forage and agroforestry systems where above-ground parts are regularly harvested or pruned as this can induce senescence of nodules and roots (Vance et al, 1979;Sanginga et al, 1995;Jalonen and Sierra, 2012).…”
Section: Isotopic Fractionationmentioning
confidence: 99%